By Whatever Name - Myklebost, Svenn-Arve (Early Modern Culture Online, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false NO-BOK X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Vanlig tabell"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–> This paper explores the significance of naming and the role of editing practices of Shakespeare's plays: Is it Imogen or Innogen, Falstaff or Oldcastle? By looking into how editors of Shakespeare have approached these and other naming problems we will investigate what has influenced their approaches and choices, what the implications of their choices might be and what we may learn from their ways of thinking about textual editing, be it defective or successful. This paper therefore deals with editing practices in general and, more specifically, with the actual significance of naming: is Henry IV featuring Sir John Oldcastle a wholly different play from Henry IV featuring Sir John Falstaff?